2018
DOI: 10.14302/issn.2639-3166.jar-18-2239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilizer on some Attributes of SorghumGrown in Saline Soil under Irrigation

Abstract: The main objective of this study was to investigate the effects of 4 levels of Nitrogen (N) fertilizer (0, 25, 50 and 75 Kg N/fed) on some attributes of Sorghum (Sorghum bicolor L). This study was conducted in the farm of College of Agriculture, University of Bahri-Sudan; during the period 2014-2015. Where the soil is classified as saline with pH ranging from 7.5 -7.8. A randomized completely block designed (RCBD); with 3 replications and four (4) treatments was adopted. All recommended cultural practices were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The characteristics of plant growth, providea favourable nutritional environment by N and alsoa beneficial effect on crop growth, which ultimately resulted in higher fodder yields. These similar results confirm the findings of Singh and Sumeriya (2012), Meena et al (2018), Meena and Meena (2012), Adam and Taleim (2018), Chaudhary et al (2018) and Palanjiya et al (2019). The interaction effect on yield attributes of fodder sorghum was not influenced by the row spacing and nitrogen levels.…”
Section: Green and Dry Fodder Yieldsupporting
confidence: 92%
“…The characteristics of plant growth, providea favourable nutritional environment by N and alsoa beneficial effect on crop growth, which ultimately resulted in higher fodder yields. These similar results confirm the findings of Singh and Sumeriya (2012), Meena et al (2018), Meena and Meena (2012), Adam and Taleim (2018), Chaudhary et al (2018) and Palanjiya et al (2019). The interaction effect on yield attributes of fodder sorghum was not influenced by the row spacing and nitrogen levels.…”
Section: Green and Dry Fodder Yieldsupporting
confidence: 92%
“…Nitrogen activates the meristematic tissues and thus cell division, as well as its importance in building amino acids, including tryptophan, which is the basis for building tryptophan and auxin, which has a role in cell division [14]. Similarly, Adam and Taleim [15] showed that the application of 75 Kg N fed −1 has increased plant height compared to other levels of nitrogen fertilizer including the controls (0, 25, and 50 Kg N fed −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Agriculture is the foundation of a given country's economic structure. As well as fuel and raw material, agriculture works to reduce unemployment in the country [1].…”
Section: Significance Of Agriculturementioning
confidence: 99%
“…Trade-offs are based on three dimensions of sustainability, which are the economic, social and environmental dimensions. The Food and Agriculture Organization has developed five principles to achieve a balance between the three social, economic and environmental dimensions (1). Improve resource efficiency.…”
Section: The Impact Of Agriculture On Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation